Conceptual analysis of board diversity and corporate governance: a catalyst for sustainable growth and ethical leadership - Shanmugam, Jaya Kumar; Said, Roshima; Raja Ismail, Raja Nasrul Idzhar; Jailuddin, Noor Asrafez; Abd Karim, Zulyanti (GADING Journal for the Social Sciences, 2025)
Due to its potential impact on company performance and decision-making, board diversity has garnered significant attention in corporate governance, as the number of cases involving issues in this area has increased. This study investigates the relationship between several key factors and board diversity in corporate governance. It examines the relationship between board member attributes, firm age, gender diversity on the board, firm size, and board diversity. Board diversity is a metric that quantifies the representation of different backgrounds, viewpoints, and experiences on corporate boards. The study intends to investigate how the size of the company influences board diversity, the representation of women on boards, the duration of the firm's operations, and the individual characteristics of board members. The study aims to contribute to the body of knowledge on corporate governance practices and provide insights into the factors that influence board diversity by examining the impact of firm age, board gender diversity, firm size, and board member characteristics. The results will undoubtedly have a positive impact on increasing board effectiveness, fostering inclusivity, and enhancing organisational performance.